Bantayog discovering Manila through its monuments - Capili, Maria Angelica A.; Osias, Jarie R.; Flores, Ferdinand P.; Baguio, Bryan Jess T.; Suliguin, Geronimo C. Jr; Villanueva, Rogelio E. Jr; Goce, Rona Beth G.; Velasco, Zoilo A.; Borra, Alena Grace S.; Beup, Fernando V.; Flores, Shirley L.; Garcia, Michael Lyndon B.; et al. (Foreign Service Institute, Department of Foreign Affairs, 2008)
History of Manila through the different monuments all over the city.